2003
DOI: 10.1121/1.1592165
|View full text |Cite
|
Sign up to set email alerts
|

Speech production in noise with and without hearing protection

Abstract: People working in noisy environments often complain of difficulty communicating when they wear hearing protection. It was hypothesized that part of the workers' communication difficulties stem from changes in speech production that occur when hearing protectors are worn. To address this possibility, overall and one-third-octave-band SPL measurements were obtained for 16 men and 16 women as they produced connected speech while wearing foam, flange, or no earplugs (open ears) in quiet and in pink noise at 60, 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 22 publications
(29 reference statements)
1
34
1
Order By: Relevance
“…This may affect voice production as well as the perception of both one's own voice and that of the communication partner, in a manner similar to that which has been demonstrated for earplugs (Kryter, 1946;Tufts & Frank, 2003). Noisy environments may also be perceived differently when played over headphones, because the perception of soundscapes and the feeling of immersion in them depend on sound-restitution devices (Guastavino, Katz, Levitin, Polack, & Dubois, 2005).…”
Section: Concerns Raised By Experimental Paradigmsmentioning
confidence: 85%
“…This may affect voice production as well as the perception of both one's own voice and that of the communication partner, in a manner similar to that which has been demonstrated for earplugs (Kryter, 1946;Tufts & Frank, 2003). Noisy environments may also be perceived differently when played over headphones, because the perception of soundscapes and the feeling of immersion in them depend on sound-restitution devices (Guastavino, Katz, Levitin, Polack, & Dubois, 2005).…”
Section: Concerns Raised By Experimental Paradigmsmentioning
confidence: 85%
“…standard or augmented. Tufts and Frank (2003) have shown that the Lombard effect is much less pronounced when people wear passive protectors since the attenuation and the occlusion effect alter the perception of the background and their own voice. It is possible that active protectors preserve the effect better because the transmitted noise levels are higher; on the other hand, the occlusion effect will still be present (although the net effect will probably depend on the speech level heard via air-conduction) and the active protectors might also emphasize the higher frequency content of background noise which is potentially less favorable to invoke the Lombard effect (Lu and Cooke, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Wearing hearing protection in noise not only affects the way speech is heard, it changes the way speech is produced. At the speaking end, Tufts and Frank (2003) studied the differences in speech acoustics when produced in noise while wearing hearing protection. For people with normal hearing, the level of adjustment in vocal effort as the level of noise increased was less when hearing protection was worn than without.…”
Section: Traunmüller Et Al Describe Vocal Effort As "The Quantity Thmentioning
confidence: 99%
“…For people with normal hearing, the level of adjustment in vocal effort as the level of noise increased was less when hearing protection was worn than without. As the level of noise increased from 60 dB to 100 dB SPL, speakers not wearing hearing protection increased their speaking leved by about 40dB, while those wearing hearing protection increased their vocal level by only 3 dB to 15 dB (Tufts and Frank, 2003). At the hearing end, studies by Candido Fernandes (2003) report that in environments with +5 dB Signal-to-Noise Ratio (SNR) and +10 dB SNR , wearing hearing protection decreases the intelligi- bility of speech.…”
Section: Traunmüller Et Al Describe Vocal Effort As "The Quantity Thmentioning
confidence: 99%